Pengaruh Minat Belajar dan Media Pembelajaran terhadap Hasil Belajar Siswa Kelas X AKL Di SMK Negeri 3 Padang pada Mata Pelajaran Akuntansi Dasar Tahun Ajaran 2020/2021 pada Masa Pandemi Covid 19 - Mutmaina Nurul Enisa; Yesmira Syamra; Erita Erita (Horizon, 2021)
This study aims to analyze: 1) The Effect of Learning Interest on the Learning Outcomes of Class X AKL Students at SMK Negeri 3 Padang in Basic Accounting Subjects for the 2020/2021 Academic Year During the Covid 19 Pandemic. 2) The Effect of Learning Media on Learning Outcomes of Class X Students AKL at SMK Negeri 3 Padang in Basic Accounting Subjects for the 2020/2021 Academic Year during the Covid 19 Pandemic. 3) The Effect of Learning Interest and Learning Media on Learning Outcomes of Class X Students AKL at SMK Negeri 3 Padang in Basic Accounting Courses for the 2020 Academic Year /2021 During the Covid 19 Pandemic.This type of research is descriptive and associative. The population in this study were all students of class X AKL at SMK Negeri 3 Padang. The sample amounted to 97 people with the sampling technique in the form of total sumpling. The research instrument used for this study was a closed questionnaire using multiple linear regression analysis and hypothesis testing with t-test and F-test. Data analysis was assisted by SPSS version 16 and eviews version 8.The results showed that: 1.) Interest in learning had a positive and significant effect on learning outcomes. Based on the results of the tests that have been carried out, the coefficient value of interest in learning has a positive value of 0.457, a tcount value of 2.149 > 1.6610 (ttable value) and a significance value of 0.034 <0.05. 2.) learning media has a positive and significant impact on learning outcomes. Based on the results of the tests that have been carried out, it is obtained that the coefficient of the learning media is positive at 0.526, the tcount is 2.248 > 1.661 (ttable value) and the significance value is 0.027 < 0.05. 3.) The significance value for the influence of interest in learning and learning media together on Y is 0.000 <0.05 and the value of Fcount is 8.884 > Ftable 3.94.